Sistem Kontrol Kondisi Tubuh Manusia Menggunakan NodeMCU Dengan Notifikasi - Ananda; Ummul Khair; Arief Budiman (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
During the current pandemic, keep a sound safe framework. also, obviously to know it all we need to actually take a look at it. The heart is one of the fundamental organs possessed by people whose capacity is to siphon blood all through the body. Pulse Beats Per Minute (BPM) is a boundary to decide the state of the heart and the way of deciding the state of the heart is to know the recurrence of the heartbeat. What's more, with the assistance of a temperature sensor, it will be more useful to know the state of our body. This body condition observing apparatus is planned dependent on NodeMCU ESP8266, temperature sensors DS18B20 and MAX30102 to recognize pulse. This examination was led to make it simpler for us people to control the soundness of our bodies at whatever point and any place we need. The pulse and internal heat level information from the observing device will be shown on the OLED LCD and the outcomes from the sensors will be shown on the OLED LCD and furthermore a sound notice that contains data regarding if your body is in acceptable condition dependent on the consequences of the two sensors.